The Influence of Financial Literacy on Students' Consumptive Behavior - Nadira Oktasari; Onny Fitriana Sitorus; Novelia Utami (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to determine the extent to which financial literacy influences the consumer behaviour of senior high school students in Pondok Gede District, Bekasi City. The research was conducted at State Senior High School 5 and State Senior High School 21 in Bekasi, with a sample of 96 students selected through proportional stratified random sampling. Data were collected using questionnaires and analyzed with statistical tests. The findings show that financial literacy has a positive and significant effect on students' consumer behaviour, suggesting that students with greater financial literacy tend to make more rational and responsible consumption decisions. This result highlights the importance of strengthening financial education among adolescents, particularly in school settings, as a preventive measure against excessive consumerism. In practice, the study suggests that integrating financial literacy programs into the school curriculum can equip students with the skills to manage their finances wisely and avoid wasteful spending habits.